Characterization of a Heterojunction Silicon Solar Cell by Means of Impedance Spectroscopy - Kazybek Aimaganbetov; Darkhan Yerezhep; Mussabek Kishkenebayev; Nikolay Chuchvaga; Nurlan Almas; Serekbol Tokmoldin; Nurlan Tokmoldin (Micromachines, 2024)
Impedance spectroscopy provides relevant knowledge on the recombination and extraction of photogenerated charge carriers in various types of photovoltaic devices. In particular, this method is of great benefit to the study of crystalline silicon (c-Si)-based solar cells, a market-dominating commercial technology, for example, in terms of the comparison of various types of c-Si devices. This study investigates the dark and light electrophysical characteristics of a heterojunction silicon solar cell fabricated using plasma-enhanced chemical vapor deposition. The measurements are performed at various applied biases, enabling the determination of complex resistance, characteristic time, capacitive response and impurity concentration within the semiconductor junction and to correlate them with the device performance. In addition, the impedance spectra of the studied cell were investigated as a function of temperature. Studies of the frequency and temperature dependences of capacitance do not reveal a significant presence of thermally activated centers of free carrier capture, concomitant with a very small value of the activation energy extracted from an Arrhenius-type analysis. This leads to a conclusion that these centers are likely not impactful on the device operation and efficiency.